PENGARUH SANKSI ADMINISTRASI DAN SURAT PAKSA TERHADAP OPTIMALISASI PENCAIRAN TUNGGAKAN PAJAK (Studi pada Kantor Pelayanan Pajak Pratama Singosari) - Wardani, Danis Maydila (Jurnal Mahasiswa Perpajakan, 2014)
The trust given by the government to taxpayers in self-assessment system should be able to run well according to the plan. Taxpayers are capable for performing their tax duty well and properly without negligence, deliberateness, and ignorance concerning this duty. In order to minimize these actions, there should be law enforcement in the obedience of the taxpayers. This study is aimed to (1) Know whether the administration charge and distress warrant has significant effects on the optimization of Disbursement of Tax Arrears. (2) Analyze and explain whether the administration charge has partially significant effects on the optimization of Disbursement of Tax Arrears, and (3) Analyze and explain whether the distress warrant has partially significant effects on the optimization of Disbursement of Tax Arrears.The kind of study used in this research is quantitative study, which is used to test hypothesis about the effects of the administration charge and distress warrant on the optimization of Disbursement of Tax Arrears. The population in this study is Taxpayers who receive administration charge and distress warrant and have tax arrears in Small Tax Office Singosari.The result of this study exclaimed that administration charge and distress warrant Variables have simultaneously significant effects on the optimization of Disbursement of Tax Arrears. Partially, administration charge and distress warrant Variables havesignificant effects on the optimization of Disbursement of Tax Arrears. It is suggested for the next researchers to employ other variables that affect the optimization of Disbursement of Tax Arrears, which are taxpayers, awareness, criminal sanctions, and so on to improve the study. Keywords: Administration Charge, Distress Warrant, and Optimization of Disbursement of Tax Arrears